Study on the undergraduate interns of a medical college in eastern India: the knowledge, attitude and practice regarding COVID-19 pandemic preparation - Majumder, Uttam; Baidya, Iti; Layek, Avik Kumar (Asian Journal of Medical Sciences, 2021)
Background: With the rapid propagation of the SARS-COV-2 or COVID-19 pandemic, the healthcare facility around the world has been stretched a large extent. To keep the green supply chain to the healthcare resources ready for the battle, sufficient knowledge, proper attitude and adequate practices are of paramount necessity. Aims and Objectives: The study was done to the knowledge, practice and attitudes towards COVID-19 pandemic preparedness among the undergraduate medical interns of a tertiary care teaching center in Eastern India. Materials and Methods: Semi-structured proforma for socio-demographic details and KAP Questionnaire for COVID-19 preparedness were circulated among the Interns. Interaction among the subsets of the KAP scale as well as their association with different socio-demographic variables were studied. Results: Out of the 138 subjects participated in the study the KAP parameters were not significantly different based on the socio-demographic factors barring presence of better practices among the female interns and less score on knowledge and attitude in presence of Psychiatric illness. It was seen that better practice was significantly correlated with knowledge mean score. Conclusion: The study implied that training on the updated knowledge along with exposure to simulated environment with scheduled supervision to reflect the behavior of the interns was of great importance so that in extreme situation, the less experienced resources could also come handy into utilization if needed.